Farming and ranching through wildfire: Producers' critical role in fire risk management and emergency response - Natalia Pinzón; Ryan E. Galt; Leslie M. Roche; Tracy Schohr; Brian Shobe; Vikram Koundinya; Katie Brimm; Jacob Powell (California Agriculture)
Wildfires increasingly threaten California’s agricultural sector, posing serious risks to farming, ranching, and food systems. We conducted a survey of 505 California farmers and ranchers affected by wildfires between 2017 and 2023. Main findings show that wildfires’ impacts on producers are extensive and range from mild to catastrophic, with both short and long-term repercussions, regardless of their exposure level. Producers play a central role in community emergency wildfire risk response and management by reducing fuel loads, creating defensible space, and leveraging their fire management expertise for themselves and their neighbors. Many producers lack a robust financial safety net, particularly among vulnerable populations, which points to the need to increase access to recovery resources, including insurance and disaster assistance programs. We find an urgent need for policy reforms, improved support, targeted extension programs, and integrated coordination mechanisms. Producers are our overlooked allies in building widespread wildfire resilience. Enhanced collaborative efforts among producers, fire professionals, and agricultural support organizations are thus imperative to co-create and implement strategies that ensure the long-term sustainability and economic viability of California’s agricultural communities.